POTENSI EKONOMI DAN KELAYAKAN USAHA BUDIDAYA IKAN NILA (OREOCHROMIS NILOTICUS) BERBASIS KEARIFAN LOKAL DI KAMPUNG LAUT DESA JERUJU BESAR KABUPATEN KUBU RAYA - Syamsuri Syamsuri; Hasria Alang (Lampung University, 2023)
Analysis of economic potential and business feasibility is carried out so that aquaculture business actors can avoid the risk of loss, one of which is tilapia (Oreochromis Niloticus) cultivation. One of the areas that also does this cultivation is Kampung Laut, Jeruju Besar Village. The research objective was to analyze the economic potential and feasibility of tilapia cultivation in Kampung Laut. The research method is descriptive quantitative. The research variables are economic potential and business feasibility. Data collection was carried out randomly through observation and interviews with informants. Data analysis of economic potential is carried out through acceptance and income analysis, while business feasibility were analyzed through operating profit (OP), benefit cost ratio (BCR), payback period (PP), profitability, breakeven point (BEP), return on investment (ROI) formulas. The results of the study show that the tilapia farming business in Kampung Laut has economic potential because it can provide a profit of Rp. 17,820,000 every harvest period. In addition, the tilapia farming business in the research location is very feasible to restart based on the results of analysis of PCR, OP, PP, total BEP and price BEP. Key words: Business Feasibility, Cultivation, Economic Potential, Kampung Laut, Tilapia